A Novel Glycolysis and Hypoxia Combined Gene Signature Predicts the Prognosis and Affects Immune Infiltration of Patients with Colon Cancer - Mao G; Wu J; Cui H; Dai LY; Ma L; Zhou Z; Liang B; Zhang S; Lin S (International Journal of General Medicine, 2022)
Guochao Mao,* Jianhua Wu,* Hanxiao Cui, Luyao Dai, Li Ma, Zhangjian Zhou, Baobao Liang, Shuqun Zhang, Shuai Lin Department of Oncology, The Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuai Lin; Shuqun Zhang, Department of Oncology, The Second Affiliated Hospital of Xi’an Jiaotong University, 157 Xiwu Road, Xi’an, Shaanxi, 710004, People’s Republic of China, Email voyage420@163.com; shuqun_zhang1971@163.comPurpose: We aimed to characterize the expression patterns of glycolysis and hypoxia genes in colon cancers as well as their value in prognosis and immune microenvironment.Methods: The expression profiles were acquired from the Cancer Genome Atlas database. Enrichment of hypoxia and glycolysis gene sets in colon cancer was identified by gene set enrichment analysis. Then, a prognostic signature was built up after Cox regression analyses, and overall survival analysis validated the predictive ability. Immune status and infiltration in cancer tissues were explored using the single sample gene set enrichment analysis and CIBERSORT algorithm. A nomogram model integrating clinical variables and the gene signature was established and assessed.Results: Altogether, 378 cancer and 39 control cases were enrolled. Three glycolysis gene sets and two hypoxia gene sets were enriched in colon cancer (P < 0.05). Five independent genes (ENO3, GPC1, P4HA1, SPAG4, and STC2) were significantly correlated with prognosis of colon cancer patients. Patients with higher risks had significantly better prognosis than those with lower risks (P = 0.002 and AUC = 0.750), which was also observed in the elderly, female and stage I–II subgroups (P < 0.05). In high-risk cases, proportion of NK cells resting increased (P < 0.05) while that of dendritic cells activated (P < 0.05), dendritic cells resting (P < 0.01) and monocytes (P < 0.01) decreased. Besides, expressions of 22 checkpoint genes were found abnormal in groups with different risks (P < 0.05). The predictive nomogram presented satisfactory performance with C-index of 0.771 (0.712– 0.830). The area under ROC curve was 0.796 and 0.803 for 3- and 5-year survival prediction, respectively.Conclusion: A glycolysis and hypoxia combined gene signature was a promising method to evaluate the prognosis and immune infiltration of colon cancer patients, which may provide a new tool for cancer management.Keywords: colon cancer, gene signature, glycolysis, hypoxia, prognosis